2019
DOI: 10.1128/aac.01056-19
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Carbapenem-Resistant Serotype K1 Hypervirulent Klebsiella pneumoniae by Acquisition of bla VIM-1 -Bearing Plasmid

Abstract: We report the identification of a carbapenem-resistant, hypervirulent Klebsiella pneumoniae (hvKp) strain which produced the carbapenemase VIM-1. Genomic analysis showed that the strain belonged to sequence type ST23 and serotype K1, a major hvKp clone, and harbored three resistance-encoding plasmids. Among them, a blaVIM-1-bearing plasmid was found to possess a mosaic structure presumably generated by multiple gene mobilization events. This finding indicates that hvKp actively acquires mobile resistance-encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Strain KP20194d, isolated from patient 4, and strain KP20194c, isolated from patient 3, shared the loss of a 10-kbp fragment from plasmid p2 which contained rmtB (Figures 1, 2), suggesting the transmission from patient 3 to patient 4 given the timeline and the use of the same bed and ventilator. The emergence of the CR-hvKP strains can result from the acquisition of either a carbapenemase-producing plasmid by a hypervirulent strain, usually belonging to serotype ST23 and capsular type K1/K2 (Yao et al, 2015;Dong et al, 2019;Shen et al, 2019); or a pLVKP-like virulence plasmid by CRKP strains, among which ST11 is dominant in China (Wei et al, 2016;Ruan et al, 2020;Yang et al, 2020). Our strains likely fit into the latter category, because MLST and Kaptive software analyses indicated that our 13 strains belonged to ST11-K64, and also because of the existence of the pLVPK-like virulence plasmid (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Strain KP20194d, isolated from patient 4, and strain KP20194c, isolated from patient 3, shared the loss of a 10-kbp fragment from plasmid p2 which contained rmtB (Figures 1, 2), suggesting the transmission from patient 3 to patient 4 given the timeline and the use of the same bed and ventilator. The emergence of the CR-hvKP strains can result from the acquisition of either a carbapenemase-producing plasmid by a hypervirulent strain, usually belonging to serotype ST23 and capsular type K1/K2 (Yao et al, 2015;Dong et al, 2019;Shen et al, 2019); or a pLVKP-like virulence plasmid by CRKP strains, among which ST11 is dominant in China (Wei et al, 2016;Ruan et al, 2020;Yang et al, 2020). Our strains likely fit into the latter category, because MLST and Kaptive software analyses indicated that our 13 strains belonged to ST11-K64, and also because of the existence of the pLVPK-like virulence plasmid (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Two of these (K.mic SPARK_1816_C1 and K.gri SPARK_1652_C1) present nearly identical genotypic and phenotypic resistance profiles to each other, as well as to five isolates of K.pne. This resistance profile is characterised by the presence of bla SHV-12 , bla VIM-1 , mph(A), and qnrS genes, harboured by a class 1 integron (GenBank accession number MN783743) associated with the highly conjugative IncA plasmid pR210-2-VIM 47 . This plasmid is known to be circulating in multiple Enterobacteriacae species in Italy 48 , and the re-emergence of VIM-1 in this region is thought to reflect the increased use of ceftazidime-avibactam (CAZ-AZI) to treat with KPC-producing bacteria.…”
Section: Distribution Of Resistance Genesmentioning
confidence: 99%
“…Apart from this MDR plasmid, this strain carried another two plasmids, including its virulence plasmid (Xie et al, 2018). In Dong et al (2019) study, a VIM-1-producing K1 ST23 CR-HvKP strain harbored three plasmids; a virulence plasmid highly homologous to that recovered from other ST23 hvKPs; and a bla VIM-1bearing plasmid possessing a unique resistance island structure presumably generated by multiple gene mobilization events. Yuan et al (2019) showed that apart from an IncHI1/IncFIB pLVPK-like plasmid, a bla NDM-5 -carrying K54 ST29 CR-HvKP isolated from Sichuan, China, harbored a bla NDM-5 -carrying IncX3 self-transmissible plasmid.…”
Section: Hv (Hm) Kps Obtain Multidrug-resistance Plasmidsmentioning
confidence: 98%